A new species of the enchytraeid genus Mesenchytraeus Eisen, 1878 (Clitellata, Enchytraeidae) from the eastern Chukot Peninsula, Russian Far East, as further evidence of former trans-Beringian faunal connections - Dózsa-Farkas, Klára; Makarova, Olga (Zootaxa, 2025)
A new potworm species, Mesenchytraeus tschukotensis Dózsa-Farkas sp. nov., is described from the Lavretiya Bay coast, eastern Chukot Peninsula, Russian Far East, based on morphological details. Its numerous records appear to be confined to a single Arctic ground squirrel (Urocitellus parryii (Richardson, 1825)) colony with dense grassy vegetation. Such an association is suggested to be caused by the specific winter microclimatic conditions in gopher burrows due to the rodent’s thermogeny. The new enchytraeid species, together with M. harrimani Eisen, 1904; M. maculatus Eisen, 1904; and M. melanocephalus Christensen & Dózsa-Farkas, 1999, form an amphi-Beringian group of closely related species, similar in the structure of the spermathecal ampullae, that seems to be confined to the Pacific coast of North America and the Arctic coast of Siberia.